Factors Affecting Independence Primipara Mothers In Caring For Babies At PMB Devi Andriani Lhokseumawe City Year 2023 - Nurliah, Nurliah; Pabidang, Siswanto; Gunarmi, Gunarmi (International Journal of Health Sciences, 2024)
The birth of a child causes a fundamental challenge to the existing structure of family interaction regarding the care of the newborn. When a baby is first born, the mother may feel confused about how to care for him. Even routine tasks such as changing diapers and bathing can make a mother anxious, especially if she has never spent time on things related to baby care before. To develop independent personal abilities requires self-confidence and a sense of calm as an experienced parent for first-time mothers (primiparous). The research objective to be achieved is to analyze the factors that influence the independence of primiparous mothers in caring for babies at PMB Devi Andriani, Lhokseumawe City. This type of research uses a descriptive analytical survey with a cross sectional design. The population in this study was 56 people, while the sample was 56 Primipara mothers, using total sampling technique. Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that the independence of primiparous mothers is related to maternal knowledge p = 0.000, culture = 0.002, trust p = 0.001, maternal age p = 0.001, family support p = 0.003, meaning there is a relationship between maternal knowledge, culture and trust. Maternal age, and family support with the independence of primiparous mothers. From the results of the multivariate analysis, it is known that the variable that has the most dominant influence in this study is the Mother's Knowledge variable with an OR value of 21,483. There is the influence of maternal knowledge, culture, beliefs, maternal age and family support and the most influential variable is maternal knowledge. The suggestion is that it is hoped that this research can be used as reference material for hospitals, especially to increase the competency of midwives so that they can maximize mothers' knowledge during postpartum visits so that they can independently care for their babies in the future.